Pertamina Systemic Corruption: Van Dijk`s Critical Discourse Analysis on Indonesia Al-Youm`s Reporting - Ammar, Zaqhlul; Mas’adi, M. Anwar (Journal of Language and Literature Studies, 2025)
This study investigates how corruption in Indonesia is portrayed in Arabic-language media by analyzing a news article from Indonesiaalyoum.com that reports on systemic corruption at Pertamina involving the son of businessman Riza Chalid. The research aims to uncover how media discourse, particularly in international Arabic outlets, constructs and communicates corruption as a deeply entrenched societal issue. The study employs Teun A. van Dijk’s Critical Discourse Analysis (CDA) framework, focusing on three structural levels—macrostructure, superstructure, and microstructure—to dissect the textual and contextual elements of the news report. The analysis is further enriched by examining aspects of social cognition and situational context, offering insights into how media narratives influence public understanding and shape international perspectives. The study’s findings reveal that the article strategically utilizes framing, lexical selection, and narrative organization to expose power relations, elite collusion, and economic injustice. These elements work together to reinforce anti-corruption discourses while highlighting the role of influential figures in perpetuating systemic problems. The study concludes that Arabic-language media serves not only as a platform for information dissemination but also as a critical actor in uncovering ideological undercurrents and influencing global perceptions of national governance. The research contributes to broader discussions on media, power, and transnational discourse on corruption.